Parking Lots Space Detection With Floyd Warshall Algorithm At Kartini Shopping Mall Bandar Lampung - Yuni Puspita Sari; Rionaldi Ali; Dona Buana Putri (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Mall Kartini is the second largest central place in Bandar Lampung City with a building area of 40,000 m² and consists of 4 floors and a parking capacity of up to 200 vehicles. With available space during peak hours, 11.00 AM to 1.00 PMfor the parking space jumped to 50% from usual hours. Based on the survey results, 80% of the 100 vehicle users who will park have obstacle turning around to get a parking space. To determine this problem, this study used the Floyd–Warshallmethod to compare all possible paths in the graph for each side of all existing vertices. The result of this study stated that a designed application gave a displays information on space parking lots by applying the Floyd–Warshall algorithm incalculating the shortest path. Furthermore, it was able to compare all possible paths on the graph for each side of all existing vertices. Based on the results of the Black Box testing, several component were carried out, including: Device 1 with Android version 8.0, Device 2 with Android version 9.0 and Device 3 with Android version 10. All test components were successfully carried out. Moreover, the difference for theappearance of the application was impacted due to the difference device in screen size.Keywords-- Android, Parking Space, Floyd-Warshall Algorithm